MRI-visible nanoparticles from hydrophobic gadolinium poly(ε-caprolactone) conjugates. (15th January 2015) - Porsio, Barbara; Lemaire, Laurent; El Habnouni, Sarah; Darcos, Vincent; Franconi, Florence; Garric, Xavier; Coudane, Jean; Nottelet, Benjamin
Abstract: In this work we report on the synthesis of two hydrophobic and degradable gadolinium poly(ε-caprolactone) conjugates and their use for the preparation of MRI-visible nanoparticles intended for diagnosis applications. Advantage has been taken from functional poly(ε-caprolactone)s (PCL) bearing propargyl (PCL-yne) or amine groups (P(CL-co-NH2 VL)) to yield conjugates by following two strategies. In a first approach, an azido-chelate of gadolinium (Gd(III)) has been conjugated by CuAAC to PCL-yne to yield a polymeric chelate containing 2.6 wt% of Gd(III). In a second approach, a dianhydride Gd(III)-ligand was reacted with P(CL-co-NH2 VL) to yield, after complexation with Gd(III) salts, a polymeric chelate containing 15.4 wt% of Gd(III). The polymers biocompatibility was assessed against L929 fibroblasts. In a second part, advantage was taken from the PCLs conjugates hydrophobicity to easily prepare by nanoprecipitation nanoparticles with diameters ranging from 120 to 170 nm. The nanoparticles MRI-visibility was then evaluated and confirmed under the spin-echo and the clinically relevant gradient-echo MRI sequences. Graphical abstract: Highlights: Functional poly(ε-caprolactone)s are proposed as macromolecular ligands of gadolinium. MRI-visible nanoparticles are prepared from PCL-based macromolecular contrast agents. Nanoparticles are visible under clinically relevant gradient echo sequence. PCL-based MRI nanoparticles can be envisioned to develop theranostic tools.